"The music gets through": Experiences of classical composers and observations of hospitalized adolescents in a music-based intervention. (September 2022) - Cascarino, Emily; Knight, Tess; Macdonald, Jacqui A
Music is a valuable aid for hospitalized adolescents as they navigate normative and non-normative stressors. Music-based interventions link these adolescents with composers who write music designed to facilitate emotional well-being; yet little is known about how each engage and find meaning in these interventions. This study examines the motivations and musical choices of composers of music for mental health, as well as how hospitalized adolescents engage in and benefit from the creative process. Ten adolescents with extensive hospital experiences, six composers, two hospital staff, and one program coordinator were observed and/or interviewed in a music-based intervention. Interpretative phenomenological analysis (IPA) of interviews with composers, coordinators, and hospital staff was performed to gain deep understanding of psychosocial benefits for all groups. This was supplemented by ethnographic observation of the program. Qualitative themes of Composer Reasoning, Listener Influence, and Adolescent Engagement revealed interplay of challenges and rewards for composers and adolescents. Composers reported positive change in adolescent mood and engagement and reflected on this within the context of meaning-making and social connection. This study demonstrates the potential value of music as a tool to promote positive identity and contributes to the body of research forging a connection between the arts and health care.